THE SUSTAINABLE TOURISM DEVELOPMENT EFFORTS THROUGH THE DEVELOPMENT OF CULTURAL TOURIST DESTINATIONS IN BUGISAN TOURISM VILLAGE, KLATEN, CENTRAL JAVA - Amini, Diansari Solihah; Wiratma, Harits Dwi; Nuswantoro, Bagus Subekti; Subandi, Yeyen; Nurgiyanti, Tanti (Jurnal Ilmiah Global Education, 2023)
The potential of a community can contribute to driving the economy of tourism villages. However, not all tourist villages can attract a significant number of tourists. It can be caused by the lack of management and potential optimization of the community. This research aims to identify tourism products that have been run in Bugisan Tourism Village. It also intends to find a development strategy for the village so that it can ensure the sustainability of tourism for the local culture and its cultural potentials of the host community can be preserved. The research method used is descriptive qualitative through observation and interview techniques as well as a literature study to collect data from primary and secondary sources. By using the concepts of sustainable tourism development, the efforts that can be implemented by Bugisan Tourism Village are through the development of several cultural elements, such as language, handicrafts, art and music, history of the region and religion, dress and clothes as well as education system. Meanwhile, it is necessary to improve the aspects of ancillary service and institution of the Bugisan Tourism Village.